Uroflow studies in children: Correlation with age, weight and body surface area. - Amaro, João Luiz [UNESP]; Trindade, JCS; Vercesi, LAP; Agostinho, Aparecido Donizeti [UNESP]; Goldberg, José [UNESP] (Masson Editeur, 1996)
Peak flow rate data (Q(max)) are important for diagnosis of lower urinary tract obstruction. However, the lack of uroflowmetry studies in children, makes their interpretation difficult. With this aim, we studied 167 boys classified in four groups according to their age (G1 : n = 48, 6-7 years; G2 : n = 43, 8-9 years; G3 : n = 37, 10-11 years; G4: n = 39, 12-14 years). We studied in all children, weight, height, body surface area, peak flow rate (Q(max) and the correspondant urinary volume (Vol). Means and standard deviations of Q(max) (ml/sec) were : 15 +/- 5 (G1), 15 +/- 5 (G2), 17 +/- 5 (G3) and 22 +/- 7 (G4) respectively. Corresponding urinary volumes (Vol) (mean standard deviation - in ml) were : G1 = 123 +/- 75; G2 = 122 +/- 79; G3 = 158 +/- 96 and G4 = 162 +/- 101. We found a significant correlation (p < 0,01) between Q(max) and Vol in groups G2, G3 and G4; and between Q(max) and height in groups G1 and G4.The authors demonstrated a positive correlation between maximum flow and voided volume, and an increase of Q(max) with age.
Keywords: uroflow; children; urinary tract obstruction